2017
DOI: 10.1002/adv.21837
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a high performance polyamide‐6 elastomer based on poly(ether‐block‐amide) multiblock copolymer by reactive processing in torque rheometer

Abstract: The polyamide-6 based poly(ether-block-amide) (PEBA) multiblock copolymers were reactively prepared in typical processing equipment, torque rheometer. The reactive processing conditions of PEBA were discussed in details on the base of the tensile strength as the main quantization parameter and the torque rheological curves.The optimized reaction temperature, reaction time, and rotational speed were 150°C, 10 min, and 40 rpm respectively. The chemical structure, tensile properties, thermal transition, thermal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As shown in Figure S1b (Supporting Information), the increase of torque indicated that the polymerization reaction occurred between OPA and OPU, and the decrease of torque was related to the decrease of viscosity caused by rotor shear heat generation. [ 51 ] Finally, the equilibrium of torque demonstrated that the reaction was complete. PUUA elastomer has the inherent advantages of adjustable mechanical properties and crystallization/melting temperature, which is attributed to variable ration of PTMEG and OPA existing in the network of the block copolymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure S1b (Supporting Information), the increase of torque indicated that the polymerization reaction occurred between OPA and OPU, and the decrease of torque was related to the decrease of viscosity caused by rotor shear heat generation. [ 51 ] Finally, the equilibrium of torque demonstrated that the reaction was complete. PUUA elastomer has the inherent advantages of adjustable mechanical properties and crystallization/melting temperature, which is attributed to variable ration of PTMEG and OPA existing in the network of the block copolymer.…”
Section: Resultsmentioning
confidence: 99%
“…[37] However, many crosslinked semi-crystalline SMPs don't possess 2W-SME at the same time [38] and the switching temperature is generally low, [6,39,40] which may be difficult to meet the applications of complex shape transformation such as aerospace. In our previous works, a new kind of thermoplastic elastomer, poly(urethane-urea-amide) (PUUA), was synthesized [36,41] and it is a novel shape memory polymer material with wide temperature memory range, excellent wear resistance, good fatigue resistance [42][43][44] compared with polyurethane, [45] polyethylene. [46] Besides, PUUA possesses several transition temperatures including a high transition temperature, which has the potential to realize multiple and two-way shape memory effects.…”
Section: Introductionmentioning
confidence: 99%
“…[ 38 ] and Lei et al. [ 39 ] chose reactive processing instead of solvent polycondensation to carry out the third step reaction in fabricating I‐M TPAEs during a very short time (i.e., 10 min) by exploiting HAAKE double‐screw extruder and torque rheometer. This preparation strategy avoids the drawback of solvent‐consuming post‐treatment and achieves environmentally friendly processing meanwhile; it also is more suitable and convenient for large‐scale industrial production, because the two typical thermoplastic processing apparatuses (HAAKE double‐screw extruder and torque rheometer) are widely used in industries.…”
Section: Synthesis Of Tpaesmentioning
confidence: 99%
“…Alongside, all these preliminary investigations, a few kinds of literature were found on examining the degradation and effect of moisture on PA66 [8][9][10]. Recent progress in the polymer sector is to blend two or more polymer of similar chains to attain the benefits of both the polymers [11][12][13][14]. Kelnar et al modified the PA6 with ethane-propene elastomer and reinforced with graphene oxide (GO) and revealed that the material system demonstrated increased strength, stiffness and toughness [15].…”
Section: Introductionmentioning
confidence: 99%